1966
DOI: 10.1104/pp.41.5.877
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene as a Factor Regulating the Growth of Pea Epicotyls Subjected to Physical Stress

Abstract: Simunary. Pea epicotyls (PisuniI satikl'u,,, cv. Alaska) were enclosed in chamibers in which their elongation was restricted by means of a foam neoprene stopper or by a medium of glass beads. These treatmentii increase(l evolution of ethylene and restllted in reduced length and increased dianmeter of both the internodes and the cells of the internodes. These responses increase(d with increasinig degrees of restriction. A time-sequenice study of the emergence of epicotyls through 90 mm of glass beads showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
1
2

Year Published

1967
1967
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(118 citation statements)
references
References 9 publications
(4 reference statements)
3
112
1
2
Order By: Relevance
“…We are not aware of reports on levels of ethylene in soils, but since the roots themselves produce the gas they are probably continuously exposed to it. Goeschl et al (11) have shown that ethylene production of peas is increas-ed by mechanical resistance to growth. It is therefore possible that roots in the soil produce even more ethylene than in the laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…We are not aware of reports on levels of ethylene in soils, but since the roots themselves produce the gas they are probably continuously exposed to it. Goeschl et al (11) have shown that ethylene production of peas is increas-ed by mechanical resistance to growth. It is therefore possible that roots in the soil produce even more ethylene than in the laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…Production of ethylene by plant tissues is nearly a universal phenomenon (3), which is affected by many environmental factors, such as light (6,13) or physical and chemical stimuli (7,17) and also by such internal factors as growth regulators (3). Inasmuch as most physiological phenomena induced by ethylene are also regulated by other growth regulators, ethylene may play an important role in the regulation of cellular metabolisms which are Plant Physiol.…”
Section: Resultsmentioning
confidence: 99%
“…Goeschl et al (6) postulated that the evolution of ethylene was in response to some physical stress and based their assumption on their observations that physical obstruction to elongation of the pea hypocotyl resulted in increased evolution of ethylene, followed by reduced length and increased diameter of both the internodes and the cells of the internodes. Burg and Burg (3) compared this phenomenon with ethylene evolution during germination of peas and assumed that physical stress is not a primary cause of ethylene production because, after radicle emergence, the ethylene production continued and remained constant while the epicotyl expanded.…”
Section: Discussionmentioning
confidence: 99%